Male Involvement in Reproductive and Maternal and New Child Health: An Evaluative Qualitative Study on Facilitators and Barriers From Rural Kenya - Lusambili, Adelaide M.; Muriuki, Peter; Wisofschi, Stefania; Shumba, Constance S.; Mantel, Michaela; Obure, Jerim; Nyaga, Lucy; Mulama, Kennedy; Ngugi, Anthony; Orwa, James; Luchters, Stanley; Temmerman, Marleen (Frontiers in Public Health, 2021)
Male involvement in reproductive, maternal, newborn and child health (RMNCH) is known to improve maternal and child health outcomes. However, there is sub-optimal adoption of male involvement strategies in several low- and middle-income countries such as Kenya. Aga Khan University implemented Access to Quality of Care through Extending and Strengthening Health Systems (AQCESS), a project funded by the Government of Canada and Aga Khan Foundation Canada (AKFC), between 2016 and 2020 in rural Kisii and Kilifi counties, Kenya. A central element in the interventions was increasing male engagement in RMNCH. Between January and March 2020, we conducted an endline qualitative study to examine the perspectives of different community stakeholders, who were aware of the AQCESS project, on the facilitators and barriers to male involvement in RMNCH. We found that targeted information sessions for men on RMNCH are a major facilitator to effective male engagement, particularly when delivered by male authority figures such as church leaders, male champions and teachers. Sub-optimal male engagement arises from tensions men face in directly contributing to the household economy and participating in RMNCH activities. Social-cultural factors such as the feminization of RMNCH and the associated stigma that non-conforming men experience also discourage male engagement.